British Association of Dermatologists guidelines for the management of hidradenitis suppurativa (acne inversa) 2018. (1st May 2019) - Ingram, J.R.; Collier, F.; Brown, D.; Burton, T.; Burton, J.; Chin, M.F.; Desai, N.; Goodacre, T.E.E.; Piguet, V.; Pink, A.E.; Exton, L.S.; Mohd Mustapa, M.F.; et al.
Abstract: Linked Comment: Jemec. Br J Dermatol 2019; 180 :975 . Plain language summary available online